Assessment of energy generated by biogas production in the educational industrial unit of the University of Szeged, Faculty of Agriculture, with special regard to biomass originating from agriculture and the food industry - Sallai, László (Acta Agraria Debreceniensis, 2007)
The importance of waste treatment is increasing. Environmental aims are the main driving force. Stricter regulations for landfills lead to the development of alternative treatment methods for waste. For agro-mechanical research, wastes from animal rearing and the food industry, secondary-tertiary biomass, is of deep concern. Available technology is versatile and relatively simple to use as a reliable and effective means of producing a gaseous fuel from various organic waste. The most common application has been the digestion of animal dung, agricultural, and food-industrial waste. This was studied by our department in our pilot farm of our Faculty. The 50-dairy cow, family sized model farm was built in the summer of 1991, as a result of a Dutch – Hungarian cooperation, on the property of the Faculty. The new pig farm, with 30 sows, and the new goat farm, with 100 nannies, was given to the Faculty on 25 April 2001. On the basis of livestock data, the annual dung production and the producible energy were determinate. The energy was calculated by biogas production coefficients in literature.